Hide eaudiobook - White, Kiersten (Random House Audio, 2022)
NATIONAL BESTSELLER • A high-stakes hide-and-seek competition turns deadly in this “marvelously creepy thrill ride of a book that keeps twisting until the very end” (Karen M. McManus, author of One of Us Is Lying )  “The suspenseful plot combines elements of Thomas Tryon’s classic Harvest Home, Netflix’s Squid Game , and the social commentary of Jordan Peele’s film oeuvre and mixes these with a revelatory pacing reminiscent of Spielberg’s Jaws .”— Booklist The challenge: Spend a week hiding in an abandoned amusement park and don’t get caught. The prize: enough money to change everything. Even though everyone is desperate to win—to seize a dream future or escape a haunting past—Mack is sure she can beat her competitors. All she has to do is hide, and she’s an expert at that. It’s the reason she’s alive and her family isn’t. But as the people around her begin disappearing one by one, Mack realizes that this competition is even more sinister than she imagined, and that together might be the only way to survive. Fourteen competitors. Seven days. Everywhere to hide but nowhere to run. Come out, come out, wherever you are.